CHEMICAL CHARACTERISTICS OF ACID-SOLUBLE COLLAGEN FROM SEA URCHIN SHEEL - Arsyad, Muh Ali; Rusli, Arham; Rosmaladewi, Rosmaladewi (Jurnal Segara, 2024)
Shells, a by-product of the sea urchin processing industry. The proportion of shells up to 85% is more widely used as a feed additive. This research aims to extract collagen from sea urchin shells using acetic and lactic acid (0.25-0.5 M). The acid-soluble collagen was then analyzed for its functional groups using the Fourier transform spectroscopy (FTIR) method. The higher the acid concentration used in extraction, the higher the yield of collagen produced. The highest collagen yield was obtained at a concentration of 0.5 M acetic acid. FTIR analysis of acid-soluble collagen showed functional of amide A (3351.64), B (2964.00), I (1663.25), II (1558.16), and III (1244.97) (cm-1). The results of functional group identification show that the acid-soluble collagen from sea urchin shells is in accordance with collagen standards.